2009
DOI: 10.1080/02827580903117404
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation of afforestation byLupinus nootkatensisand by black plastic mulch in south-west Iceland

Abstract: Afforestation has proven difficult in south-west Iceland in a region of degraded soils and high winds. Experiments at Keflavik International Airport began in 2002 to examine whether Nootka lupine (lupin; Lupinus nootkatensis) or black plastic mulch facilitates establishment of Sitka spruce (Picea sitchensis), Hooker willow (Salix hookeriana) or downy birch (Betula pubescens) by ameliorating microsite conditions. By 2008, both lupine and black plastic mulch facilitated growth of all species at most plots. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Jónsson (2004) found substantial differences from prostrate shrubs to trees in stature of downy birch in a study encompassing many stands throughout Iceland. The high degree of variation among downy birch provenances in Iceland may be the result of hybridization and gene flow from dwarf birch, Betula nana (Thórsson BIRCH PROVENANCE TRIAL Riege & Sigurgeirsson (2009) found that survival of birch seedlings, but not growth of the survivors, was greatly reduced with thick lupine, especially when accompanied by dense grass cover. Thus, it is recommended that lupine be seeded, rather than transplanted, at the same time as downy birch seedlings are planted.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Jónsson (2004) found substantial differences from prostrate shrubs to trees in stature of downy birch in a study encompassing many stands throughout Iceland. The high degree of variation among downy birch provenances in Iceland may be the result of hybridization and gene flow from dwarf birch, Betula nana (Thórsson BIRCH PROVENANCE TRIAL Riege & Sigurgeirsson (2009) found that survival of birch seedlings, but not growth of the survivors, was greatly reduced with thick lupine, especially when accompanied by dense grass cover. Thus, it is recommended that lupine be seeded, rather than transplanted, at the same time as downy birch seedlings are planted.…”
Section: Discussionmentioning
confidence: 99%
“…The birch trial plot was established on rocky, eroded soil with patches of moss-heath cover dominated by Racomitrium moss, crowberry (Empetrum nigrum), and heather (Calluna vulgaris). More information about the site conditions at Reykjanes can be found in Riege & Sigurgeirsson (2009).…”
Section: Study Sitementioning
confidence: 99%
See 2 more Smart Citations
“…The fourth is the only representative from the 185 species of the "New World" group named L. mutabilis (Andean lupin, pearl lupin), called either tarwi or chocho bean, in regard to the tall species with long branches and the short plant growth type with few branches [10]. Three other lupins worth mentioning, although only of regional agricultural importance, are L. pilosus L., an Old World lupin used as a coffee substitute (Altreier Kaffee) in Northern Italy [11], L. nootkatensis D. ex S. (Nootka lupin), used for land reclamation [12][13][14] and L. polyphyllus Lindl. (Washington lupin), used as an ornamental in many European countries including Germany, Poland, Russia, Spain, Sweden, Ukraine and the United Kingdom.…”
Section: Introductionmentioning
confidence: 99%